Pro-systemic Voters Versus Anti-systemic Ones: Emotional Attitude to Candidates and the Influence of TV Political Advertising in the 2015 Presidential Election in Poland - Olszanecka-Marmola, Agata (Political Preferences, 2015)
Presented article is aimed at examining the emotional attitudes to candidates for the president of Poland among pro-systemic and anti-systemic voters in 2015 presidential election and showing the influence of campaign TV ads on these groups of Polish electorate. The research conducted by author reveals that anti-systemic electorate is less interested in politics and more likely to be influenced by electoral TV spots. The study also confirms the relation between emotional attitudes to political actors and political preferences. According to the results of experiment anti-systemic voters expressed more positive feelings towards candidates from out of the political mainstream, and the other way round, the pro-systemic electorate rather liked the candidates presented by parliamentary parties. Key words: political advertising, electoral TV ads, emotional attitude, feelings thermometer, 2015 presidential election in Poland, anti-systemic voters